Mega Cities facing Covid-19 pandemic: How to use urban spaces in Teheran after the new pandemic - Shirgir, Elmira (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The first cases of COVID-19 occurred in the winter of 2020 in Wuhan-China. The distinctiveness of the new pandemic is that it has occurred in ‘20th century megacities, cities with a large population who use the city as their second home during the day to commute to work, socialize & etc. After the emergence of COVID-19 in February 2020 in Iran, and its capital city, Tehran, new restrictions and rules were put on the way citizens of Tehran were to use their city and its public spaces. These restrictions limit the use of these spaces to a great extent and it seems like these new limitations are here to stay for an unpredictable amount of time until a new medicine or vaccine is found. The main questions here are: How can the threat of this new pandemic in cities be reduced and controlled in the future ? And how can urban spaces be used from now on? In this paper, the new ways people are using the city in Tehran after arrival of the pandemic have been studied and suggestions for guaranteeing the safety of urban spaces from now on have been discussed.